Asymmetrical Information in Securities Markets and Trading Volume - Morse, Dale (Journal of Financial and Quantitative Analysis, 1980)
Unequal costs of obtaining and processing information may lead to trading of securities and wealth redistributions among investors. Those investors with easy access to information about a firm may be able to profit from prior knowledge of the information before public release. Public policy making bodies such as the SEC have attempted to alleviate this phenomenon by promoting public disclosure of information through litigation and regulation of the trading activities of insiders. Whether these procedures have been successful in curtailing trading due to privileged information is still open to debate. Academicians have also been concerned with resolving the existence of asymmetrically distributed information and “efficient markets.” In spite of the social and academic importance of this phenomenon, there has been little empirical work in this area. This is primarily due to a lack of a testable theoretical framework explaining investor behavior in securities markets with asymmetric information distribution. The ensuing paper provides a tentative testable theory on trading in markets with asymmetrically distributed information as well as an empirical investigation of this theory.